Menilik Kriteria “liyan”: Mewujudkan Kerukunan Umat Beragama di Yogyakarta - Magdalena Pura Adiputra Artarini (KHARISMATA: Jurnal Teologi Pantekosta, 2024)
This paper discusses the importance of religious harmony in Yogyakarta, a city with a significant number of newcomers, making it rich in diversity, one of which is religion. This diversity makes Yogyakarta also vulnerable to conflict. Through qualitative research methods with a literature study approach, the author looks at and explores the factors that influence the occurrence of intolerance. It was found that intolerance in Yogyakarta was strongly influenced by factors such as narrow-minded religious thinking, religious fanaticism, and exclusive interpretations of the concept of "the Other.” Therefore, a more inclusive introduction to the concept of “the Other” can help people appreciate religious differences, diversity in Yogyakarta and achieve religious harmony. This can be achieved through recognition of differences, interfaith dialogue, and an ethic of hospitality. It is hoped that the people of Yogyakarta will not only be able to overcome religious conflict, but also strengthen religious harmony and build sustainable communication among different religious communities.  Makalah ini membahas pentingnya kerukunan umat beragama di Yogyakarta, sebagai kota dengan jumlah pendatang yang cukup banyak, menjadikan kota Yogyakarta kaya akan keragaman salah satunya agama. Tentunya keberagaman ini menjadikan Yogyakarta juga rentan terjadi konflik. Melalui metode penelitian kualitatif dengan pendekatan studi literatur, penulis melihat dan menggali faktor apa saja yang mempengaruhi terjadinya intoleransi. Ditemukan bahwa intoleransi di Yogyakarta kuat dipengaruhi oleh faktor seperti pemikiran sempit mengenai keagamaan, fanatisme beragama, dan interpretasi eksklusif tentang "liyan." Maka pengenalan secara lebih inklusif pada konsep "liyan" dapat membantu masyarakat menghargai perbedaan dan keberagaman umat beragama di Yogyakarta serta mencapai harmoni agama. Hal ini dapat dilakukan melalui pengakuan pada perbedaan, dialog lintas iman, dan etika keramahan. Diharapkan masyarakat Yogyakarta tidak hanya dapat mengatasi konflik keagamaan, namun juga memperkuat harmoni agama, dan membangun komunikasi yang berkelanjutan di antara komunitas agama yang berbeda.